Review on the Diagnosis and Treatment of Reversible Cerebral Vasoconstriction Syndrome in Children and Adolescents - Qubty, William; Irwin, Samantha Lee; Fox, Christine K. (Seminars in Neurology, 2020)
Reversible cerebral vasoconstriction syndrome (RCVS) is a clinical–radiologic diagnosis that affects children and adolescents, but it is much more frequently reported in adults. Clinically, patients present with severe and commonly recurrent thunderclap headaches. Typical precipitating triggers include vasoactive substances, serotonergic agents, and the postpartum period. There may be associated neurologic complications at presentation or in the weeks following, such as convexity subarachnoid hemorrhage, stroke, cerebral edema, cervical artery dissection (CeAD), and seizures. Angiographically, the cerebral arteries demonstrate segmental vasoconstriction and dilation, although imaging early in the clinical course may be normal. Work-up is performed to exclude intracranial disorders such as vasculitis, subarachnoid hemorrhage due to ruptured aneurysm, meningitis, and intracranial venous sinus thrombosis. Within 1 month of initial symptom onset, clinical symptoms such as severe headache have ceased, and within 3 months, the cerebral vasoconstriction is much improved or resolved. Management involves avoidance of precipitating triggers and potentially short-term pharmacotherapy with calcium channel blockers for patients with associated neurologic complications. Steroids are not recommended and may worsen the clinical outcome. Prognosis is excellent in the large majority of patients, and only 5% of patients experience a recurrence of RCVS.
Keywords: reversible cerebral vasoconstriction syndrome; benign angiopathy; Call–Fleming's syndrome; thunderclap headache; pediatric RCVS